The Impact of United States of America Intervention On Israeli-Palestinian Conflict - Nuraini Sekar Warasti; Haya Qonita; Badrus Sholeh (Universitas Komputer Indonesia, 2022)
The Israeli occupation of Palestine became a prolonged conflict; this conflict was caused by the seizure of the Jerusalem area. Jerusalem itself is a holy city for Judaism, Christianity, and Islam. The conflict began in 1917-1947 when during British rule in Palestine with Jerusalem as the center of government, the Balfour Declaration stated that Britain handed over the mandate of Palestine to the United Nations. During the ongoing conflict to date, not only two countries, namely Israel and Palestine, are involved, but there is also the intervention of the United States which has a fairly dominant role. For example, Donald Trump as President of the United States of America unilaterally announced that he recognized Jerusalem as the capital of Israel in 2017, thus triggering a greater struggle than ever in the Middle East. The purpose of this study is to provide an overview, description, and understanding of the occurrence of conflict events in the Palestinian territories, by looking at the origins of the conflict, the role of the United States in it, and the impact of the dominant role of the United States in this prolonged conflict.